Evaluation of circulating leucocyte populations both in subjects with previous SARS-COV-2 infection and in healthy subjects after vaccination - Grimaldi, Vincenzo; Benincasa, Giuditta; Moccia, Giusi; Sansone, Annunziata; Signoriello, Giuseppe; Napoli, Claudio (Journal of immunological methods, 2022)
Innate immune mechanisms are central players in response to the binding of pathogens to pattern-recognition receptors providing a crucial initial block on viral replication. Moreover, innate immune response mobilizes cells of the cellular-mediated immune system, which develop into effector cells that promote viral clearance. Here, we observed circulating leukocyte T cell response in healthy subjects, COVID-19 infected, and in healthy vaccinated subjects. We found a significant CD8+ T cells (p < 0,05) decrease and an augmented CD4+/CD8+ ratio (p < 0,05) in COVID-19 infected group compared with vaccinated subjects. In addition, healthy vaccinated subjects have a significant increased expression of CD8+ T cells, and a reduction of CD4+/CD8+ ratio with respect to subjects previously COVID-19 infected. Central Memory and Terminal Effector Memory cells (TEMRA) increased after vaccine but not among groups.